Strategy for Learning Space Geometry Concepts in Elementary School Students - Laksmi Savitri Kumala Dewi; Aprilia Fajar Yanti; Cantika Sari Ramadhani; Setyorini Murniati; Wiwin Astuti (UIN Raden Mas Said Surakarta, 2023)
Space is an aspect of geometry that is important for students to master, which allows students to analyze and study in reality and helps to operate other material. This research aims to find out the methods and strategies used by teachers in teaching spatial geometry to elementary school students. This type of research uses library research. The data sources used as research material were obtained from 4 (four) journals related to the theme being studied so that the data presented was quite strong and clear. The analysis technique used in this research is content analysis. The results of the research show that the strategy that must be implemented by teachers is to teach the basic concepts of spatial geometry first and use concrete and supportive learning media so that students can understand the concept of spatial geometry in mathematics correctly in real life.